The Experiences of Cancer-Related Fatigue among Adult Cancer Patients: A Systematic Review - I Komang Leo Triandana Arizona; Tintin Sukartini; Ferry Efendi; Primalova Septiavy Estiadewi; Ni Putu Dian Ayu Anggraeni (Jurnal Ners, 2019)
Introduction: Cancer-related fatigue (CRF) is one of the symptoms commonly experienced and it is a subjective feeling felt by cancer patients. The aim of this systematic review was to summarize how fatigue has been described from the perspective of adult cancer patients, the impact of fatigue on their quality of life, what the patient reported as contributing factors and potential coping strategies to reduce fatigue.Methods: A systematic review is in line with PRISMA guidelines. Five databases were systematically searched (Scopus, PubMed, Springerlink, ProQuest and Science Direct) from January 2009 to February 2019 for qualitative studies describing the experience of adult cancer patients using a predefined search strategy and any relevant keywords.Results: In total, 13 out of 4692 studies were included. The ages of the included patient cancer ranged from 26 to 84 years. The majority of studies used in-depth interviews and semi-structured interviews to elicit the participant’s experiences of fatigue. Four themes were identified: the perception of cancer-related fatigue, the etiology of cancer fatigue, impact and coping strategies.Conclusion: Fatigue is impactful on quality of life from the perspective of cancer patients. Future research should focus on the prospective exploration of the impact of fatigue on woman's and men's health and identifying approaches to reduce fatigue.